Privatisation Policy in Spain: Stuck Between Liberalisation and the Protection of Nationals' Interests - Pablo Arocena (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper carries out an overview of the recent history of privatisation in Spain. At this point, the paper focuses on the analysis of the economic, financial and political objectives pursued by successive Spanish Administrations. It is argued that privatisation policy has been inconsistent with the liberalising measures, reflecting the conflict between the advocacy of market liberalisation and the protection of nationals' interests. Likewise, we review the still very scarce empirical evidence on the economic consequences of privatisation on firms' and markets' performance, with a particular emphasis on the analysis of privatisation and liberalisation in the utilities sectors.
Keywords: 330; privatisation; liberalisation; Spain; utilities